Comparison of Coincident Optical Particle Counter and Lidar Measurements of Polar Stratospheric Clouds Above McMurdo (77.85°S, 166.67°E) From 1994 to 1999. Issue 6 (18th March 2021) - Snels, Marcel; Cairo, Francesco; Di Liberto, Luca; Scoccione, Andrea; Bracaglia, Marco; Deshler, Terry
Abstract: Macroscopic stratospheric aerosol properties such as surface area density (SAD) and volume density (VD) are required by modern chemistry climate models. These quantities are in continuous need of validation by observations. Direct observation of these parameters is not possible, but they can be derived from optical particle counters (OPCs) which provide concentration (number density) and size distributions of aerosol particles, and possibly from ground‐based and satellite‐borne lidar observations of particle backscatter coefficients and aerosol type. When such measurements are obtained simultaneously by OPCs and lidars, they can be used to calculate backscatter and extinction coefficients, as well as SAD and VD. Empirical relations can thus be derived between particle backscatter coefficient, extinction coefficient, and SAD and VD for a variety of aerosols (desert dust, maritime aerosols, stratospheric aerosols) and be used to approximate SAD and VD from lidar measurements. Here we apply this scheme to coincident measurements of polar stratospheric clouds above McMurdo Station, Antarctica, by ground‐based lidar and balloon‐borne OPCs. The relationships derived from these measurements will provide a means to obtain values of SAD and VD for supercooled ternary solutions (STS) and nitric acid trihydrate (NAT) PSCs from the backscatter coefficients measured by lidar. Coincident lidar and OPC measurements provided 15 profile comparisons. Empirical expressions of SAD and VD as a function of particle backscatter coefficient, β, were calculated from fits of the form log(SAD/VD) = A + B log( β ) using β from the lidar and SAD/VD from the OPC. The PSCs were classified as STS and NAT mixtures, ice being absent. Key Points: An empirical relation of surface area density and volume density as a function of the particle backscatter coefficient is derived Back scatter coefficients have been calculated with Mie theory from OPC size distributions Coincident ground‐based lidar and balloon borne OPC measurements have been performed